An electrolyte and a battery comprising the same
Patent Information
- Application Number
- CN202410625855.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-05-20
AI Technical Summary
[0003]然而,随之而来的安全问题也逐渐凸显出来
[0080]本发明提供了一种电解液及包括该电解液的电池。所述电解液包括第一添加剂和第二添加剂,所述第一添加剂包括烃基胺类化合物,所述第二添加剂包括硫酸酯类化合物;所述电解液能够提高电池的炉温安全性能和电池的低温性能。本发明的电解液能在正负极表面形成具有良好保护效果的SEI/CEI膜,能够在高温甚至热失控的情况下,依然保持其结构和功能的稳定,使得因SEI/CEI膜失效而引起的电池安全问题得到改善;本发明的电解液添加剂还能降低电解液粘度,与溶剂分子发生溶剂化作用,即使在较低温度下,离子仍能保持较高的移动速度,提高离子导电性,降低电池阻抗,从而改善电池的低温性能。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrolyte technology, specifically relating to an electrolyte and a battery including the electrolyte. Background Technology
[0002] Since its invention at the end of the last century, lithium-ion batteries have become an indispensable part of modern life, widely used in mobile phones, laptops, electric vehicles, and many other fields. With continuous technological advancements, the energy density of lithium-ion batteries has been constantly improving, and charging speeds have been continuously accelerating, making our lives more convenient.
[0003] However, the safety issues that arise from this have gradually become apparent. In recent years, the safety of lithium-ion batteries has attracted widespread attention. Accidents such as fires and explosions occur frequently, posing a serious threat to people's lives and property. These accidents are often related to problems such as short circuits and thermal runaway within the battery. Therefore, improving the safety of lithium-ion batteries has become an important issue that urgently needs to be addressed by the scientific research and industry sectors. Summary of the Invention
[0004] To improve the furnace temperature safety of batteries, this invention provides an electrolyte and a battery comprising the electrolyte. The electrolyte includes a first additive and a second additive; the first additive includes a hydrocarbon-based amine compound, and the second additive includes a sulfate ester compound. The electrolyte can improve the furnace temperature safety performance and low-temperature performance of the battery.
[0005] The objective of this invention is achieved through the following technical solution:
[0006] An electrolyte comprising an electrolyte additive, the electrolyte additive comprising a first additive and a second additive; the first additive comprising a hydrocarbon amine compound, the hydrocarbon amine compound being selected from at least one compound of the structural formula shown in formula (I):
[0007]
[0008] In formula (Ⅰ), R1, R2, and R3 may be the same or different, and are independently selected from H, halogens, substituted or unsubstituted C1-C atoms. 12 Alkyl, substituted or unsubstituted C2-C 12 alkenyl, substituted or unsubstituted C2-C 12 Alkyne group, substituted or unsubstituted C3-C 12 Cycloalkyl; if substituted, the substituent is C1-C. 12 Alkyl or halogen; or,
[0009] R1 is selected from H, halogen, substituted or unsubstituted C1-C. 12Alkyl, substituted or unsubstituted C2-C 12 alkenyl, substituted or unsubstituted C2-C 12 Alkyne group, substituted or unsubstituted C3-C 12 Cycloalkyl; if substituted, the substituent is C1-C. 12 Alkyl or halogen; R2 and R3 form substituted or unsubstituted C3-C rings. 12 Cycloalkyl; if substituted, the substituent is C1-C. 12 Alkyl or halogen;
[0010] The second additive comprises a sulfate ester compound, said sulfate ester compound being selected from at least one compound of the structural formula shown in formula (IⅠ):
[0011]
[0012] In equation (IⅠ), n is 0 or 1, m is 0 or 1, p is 0 or 1, and X1, X2, and X3 may be the same or different, and are independently selected from each other. And at least one of the groups X1, X2, and X3 is selected from * indicates a connection point.
[0013] According to embodiments of the present invention, in formula (Ⅰ), R1, R2, and R3 may be the same or different, and are independently selected from H, halogens, substituted or unsubstituted C1-C6 alkyl groups, substituted or unsubstituted C2-C6 alkenyl groups, substituted or unsubstituted C2-C6 alkynyl groups, and substituted or unsubstituted C3-C6 cycloalkyl groups; if substituted, the substituent is a C1-C6 alkyl group or a halogen; or,
[0014] R1 is selected from H, halogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 ynyl, substituted or unsubstituted C3-C6 cycloalkyl; if substituted, the substituent is C1-C6 alkyl or halogen; R2 and R3 form a substituted or unsubstituted C3-C6 cycloalkyl after cyclization; if substituted, the substituent is C1-C6 alkyl or halogen.
[0015] According to embodiments of the present invention, in formula (Ⅰ), R1, R2, and R3 may be the same or different, and are independently selected from H, halogens, substituted or unsubstituted C1-C3 alkyl groups, substituted or unsubstituted C2-C3 alkenyl groups, substituted or unsubstituted C2-C3 alkynyl groups, and substituted or unsubstituted C3-C4 cycloalkyl groups; if substituted, the substituent is a C1-C3 alkyl group or a halogen; or,
[0016] R1 is selected from H, halogen, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C2-C3 alkenyl, substituted or unsubstituted C2-C3 alkynyl, substituted or unsubstituted C3-C4 cycloalkyl; if substituted, the substituent is C1-C3 alkyl or halogen; R2 and R3 form a substituted or unsubstituted C3-C4 cycloalkyl after cyclization; if substituted, the substituent is C1-C3 alkyl or halogen.
[0017] According to embodiments of the present invention, the hydrocarbon amine compound includes at least one of the compounds with the structural formulas shown in formulas (I-1) to (I-8):
[0018]
[0019] According to embodiments of the present invention, research has found that the increased thermal motion of hydrocarbon-based amine compounds and lithium ions at high temperatures makes it easier for hydrocarbon-based amine compounds to escape from the vicinity of lithium ions, leading to instability in the solvation structure. Simultaneously, the interaction between hydrocarbon-based amine compounds at high temperatures also causes rearrangement of solvent molecules, disrupting the original solvation structure. This disruption significantly increases the resistance of lithium ions through the separator, inhibiting lithium ion migration between the positive and negative electrodes, reducing heat generation, and thus improving the battery's furnace temperature safety performance. Furthermore, the hydrocarbon-based amine compounds can reduce the viscosity of the electrolyte, making it easier for them to undergo solvation reactions with lithium ions to form solvated ions. This allows the electrolyte to maintain a high ion migration rate and conductivity even at low temperatures, reducing the battery's impedance at low temperatures and improving its low-temperature performance.
[0020] According to embodiments of the present invention, the sulfate ester compound includes at least one of the compounds with the structural formulas shown in formulas (II-1) to (II-16):
[0021]
[0022] According to embodiments of the present invention, research has found that the sulfate ester compounds can form a thermally stable SEI film on the surface of the negative electrode, and this SEI film is difficult to rupture even at high temperatures. This effectively hinders direct contact between the negative electrode and the electrolyte, while avoiding heat generation during side reactions inside the battery. The sulfate ester compounds and hydrocarbon amine compounds respectively suppress heat generation in different regions inside the battery, jointly improving the furnace temperature safety performance of the battery. Because the interface film formed by the sulfate ester compounds on the surface of the negative electrode is stable and thin, it effectively reduces the contact resistance between the negative electrode and the electrolyte, reduces impedance during charge transfer, and prevents unstable chemical reactions or structural changes in the negative electrode active material under low-temperature conditions, thus improving the low-temperature performance of the battery.
[0023] According to embodiments of the present invention, the percentage of the first additive in the total mass of the electrolyte is 0.1wt%-5wt%, preferably 0.5wt%-1.5wt%; for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.5wt%, or 5wt%. Studies have found that when the percentage of the first additive in the total mass of the electrolyte is 0. When the content of the first additive is between 1 wt% and 5 wt%, the resulting electrolyte can significantly improve the furnace temperature safety performance and low-temperature performance of the battery. When the mass percentage of the first additive in the total mass of the electrolyte is <0.1 wt%, the improvement effect on the furnace temperature safety performance and low-temperature performance of the battery is weak due to the small mass percentage of the first additive. When the mass percentage of the first additive in the total mass of the electrolyte is >5 wt%, the improvement effect on the furnace temperature safety performance of the battery will be enhanced due to the large mass percentage of the first additive. However, because the interface protective layer formed by the first additive on the separator is too thick, it will increase the battery impedance, hinder the passage of lithium ions, and deteriorate the low-temperature performance of the battery.
[0024] According to an embodiment of the present invention, the percentage of the second additive in the total mass of the electrolyte is 0.1wt%-5wt%, preferably 0.5wt%-3wt%; for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.5wt%, or 5wt%. Studies have found that when the second additive... When the mass percentage of the second additive in the total electrolyte is 0.1wt%-5wt%, the resulting electrolyte can significantly improve the furnace temperature safety performance and low-temperature performance of the battery. When the mass percentage of the second additive in the total electrolyte is <0.1wt%, the improvement effect on the furnace temperature safety performance and low-temperature performance of the battery is weak due to the small mass percentage of the second additive. When the mass percentage of the second additive in the total electrolyte is >5wt%, the excessive mass percentage of the second additive will form a high-resistivity SEI film on the negative electrode surface, which will deteriorate the low-temperature performance of the battery.
[0025] According to an embodiment of the present invention, the electrolyte satisfies:
[0026] 0.1≤X / (Y+2)≤1;
[0027] Where X is the percentage of the first additive by mass in the total mass of the electrolyte; and Y is the percentage of the second additive by mass in the total mass of the electrolyte.
[0028] According to embodiments of the present invention, 0.2 ≤ X / (Y+2) ≤ 0.5, for example, 0.2, 0.25, 0.3, 0.375, 0.4, or 0.5. Studies have found that when the electrolyte satisfies 0.1 ≤ X / (Y+2) ≤ 1, the effects of the first and second additives can be fully utilized, resulting in optimal furnace temperature safety and low-temperature performance of the obtained battery. When the electrolyte satisfies X / (Y+2) > 1, due to the excessive mass proportion of the first additive, although the effect on improving the furnace temperature safety performance of the battery is enhanced, the interfacial protective layer formed by the first additive on the separator is too thick, which increases battery impedance, hinders lithium ion passage, and deteriorates the low-temperature performance of the battery.
[0029] According to an embodiment of the present invention, the electrolyte additive further includes a third additive, which is selected from polynitrile compounds.
[0030] According to embodiments of the present invention, the polynitrile compound includes at least one of the following: a dinitrile compound represented by formula (Ⅲ-1), a trinitrile compound represented by formula (Ⅲ-2), and a tetranitrile compound represented by formula (Ⅲ-3):
[0031]
[0032] Wherein, R4 is a group having 1-10 carbon atoms with at least 2 substitution positions; R5 is a group having 1-10 carbon atoms with at least 3 substitution positions; and R6 is a group having 1-10 carbon atoms with at least 4 substitution positions, wherein the group having 1-10 carbon atoms is selected from substituted or unsubstituted C atoms. 1-10 Alkyl, substituted or unsubstituted C 1-5 Alkyl, substituted or unsubstituted C 5-10 heteroaryl, substituted or unsubstituted C 6-10 Aryl.
[0033] According to embodiments of the present invention, the dinitrile compound represented by formula (Ⅲ-1) is selected from at least one of the following compounds: succinate (SN), glutaronitrile, adiponitrile (ADN), sebaconitrile, anonadionitrile, dicyanobenzene, terephthalonitrile, pyridine-3,4-dianitrile, 2,5-dicyanopyridine, 3,3-[1,2-ethylenedimethylbis(oxy)]bispropionitrile, trans-butenedionitrile, and ethylene glycol dipropionitrile ether.
[0034] According to an embodiment of the present invention, the trinitrile compound represented by formula (Ⅲ-2) is selected from at least one of the following compounds: 1,3,6-hexanetrionitrile (HTCN), 1,3,5-cyclohexanetrionitrile, 1,3,5-phenyltricyanide, 1,2,3-propanetrionitrile, and glyceroltrionitrile.
[0035] According to embodiments of the present invention, the tetranitrile compound represented by formula (Ⅲ-3) is selected from at least one of the following compounds: 1,1,3,3-propanetetracarbonyl, 1,2,2,3-tetracyanopropane, 1,2,4,5-tetracyanobenzene, 2,3,5,6-pyrazinetetranitrile, 7,7,8,8-tetracyano-p-benzodiquinone dimethane, tetracyanoethylene, and 1,1,2,2-tetra(ethoxycyano)ethane.
[0036] According to embodiments of the present invention, research has found that the reaction rate inside the battery accelerates at high temperatures, and the interaction between the metal elements in the positive electrode active material and the solutes in the electrolyte is enhanced, leading to the dissolution of the metal elements in the positive electrode active material and increasing the risk of degradation in the battery's high-temperature cycle performance. Based on this, a polynitrile compound is introduced as a third additive, working in conjunction with a sulfate ester compound on the surfaces of the positive and negative electrodes to form a stable and thin interfacial film. This effectively reduces the impedance of the electrode interface and improves the battery's low-temperature performance. Simultaneously, the sulfate ester compound forms a stable SEI film on the negative electrode surface that is not easily broken at high temperatures, suppressing heat generation caused by side reactions after direct contact between the electrolyte and the negative electrode. It also inhibits the deterioration of the negative electrode interface by the polynitrile compound. The polynitrile compound can form stable complexes with the metal elements in the positive electrode active material. These complexes help form a dense protective layer on the positive electrode surface, effectively isolating the positive and negative electrode active materials from direct contact. Furthermore, due to its good high-temperature stability, it is not easily broken even at high temperatures, thus improving the battery's high-temperature cycle performance and furnace temperature safety performance.
[0037] According to embodiments of the present invention, the third additive accounts for 0.1wt%-7wt% of the total mass of the electrolyte, preferably 2wt%-5.5wt%; for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, or 7wt%. Studies have found that when the third additive accounts for 0.1wt%-7wt% of the total mass of the electrolyte, it can further improve the furnace temperature safety performance, low-temperature performance, and high-temperature cycle performance of the battery. When the mass percentage of the third additive in the total electrolyte is <0.1wt%, the improvement on the furnace temperature safety performance, low temperature performance, and high temperature cycle performance of the battery is not significant due to the small mass percentage of the third additive. When the mass percentage of the third additive in the total electrolyte is >7wt%, the excessive mass percentage of the third additive will deteriorate the SEI film at the negative electrode interface, which will have a deteriorating effect on the low temperature performance and high temperature cycle performance of the battery.
[0038] According to an embodiment of the present invention, the electrolyte satisfies:
[0039] 0.3≤X+Y+Z≤9;
[0040] Wherein, X is the percentage of the first additive by mass in the total mass of the electrolyte; Y is the percentage of the second additive by mass in the total mass of the electrolyte; and Z is the percentage of the third additive by mass in the total mass of the electrolyte.
[0041] According to embodiments of the present invention, preferably, 3 ≤ X + Y + Z ≤ 9, for example, 3, 4, 5, 6, 7, 8, or 9. Studies have found that when the electrolyte satisfies 0.3 ≤ X + Y + Z ≤ 9, the polynitrile compounds and sulfate ester compounds work together on the positive and negative electrode surfaces, forming a stable and thin interfacial film. This effectively reduces the impedance of the electrode interface and improves the low-temperature performance of the battery. Simultaneously, the sulfate ester compounds form a stable SEI film on the negative electrode surface that is not easily broken at high temperatures, suppressing heat generation caused by side reactions after direct contact between the electrolyte and the negative electrode. It also suppresses the deterioration of the negative electrode interface by the polynitrile compounds. The polynitrile compounds can form stable complexes with metal elements in the positive electrode active material. These complexes help form a dense protective layer on the positive electrode surface, effectively isolating the positive and negative electrode active materials from direct contact. Furthermore, due to their good high-temperature stability, they are not easily broken even at high temperatures, thus improving the high-temperature cycle performance and furnace temperature safety performance of the battery. When the electrolyte satisfies X+Y+Z>9, the excessive mass proportion of additives will severely deteriorate the SEI film at the negative electrode interface, negatively impacting the battery's low-temperature and high-temperature cycling performance. When the electrolyte satisfies X+Y+Z<0.3, the insufficient mass proportion of additives will not significantly improve the battery's furnace temperature safety, low-temperature performance, and high-temperature cycling performance.
[0042] According to embodiments of the present invention, the hydrocarbon amine compounds, sulfate ester compounds, and polynitrile compounds may be obtained commercially or prepared using methods known in the art.
[0043] According to an embodiment of the present invention, the electrolyte further includes a negative electrode protection additive, which includes fluoroethylene carbonate and sulfonic acid compounds.
[0044] According to embodiments of the present invention, research has found that the negative electrode protective additive can participate in the formation of an SEI film on the surface of the negative electrode. The formed SEI film can separate the electrolyte from the negative electrode, avoid direct contact between the electrolyte and the negative electrode, reduce the occurrence of side reactions, reduce the reactivity of polynitrile compounds with the negative electrode, and maintain the structural stability of the negative electrode active material, thereby improving the high-temperature cycle performance and room-temperature cycle performance of the battery.
[0045] According to an embodiment of the present invention, the mass percentage of the fluoroethylene carbonate in the total mass of the electrolyte is 0-15 wt%, preferably 1-15 wt%, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt%.
[0046] According to an embodiment of the present invention, the sulfonic acid compound accounts for 0-5 wt% of the total mass of the electrolyte, preferably 1-5 wt%, for example 1 wt%, 2 wt%, 3 wt%, 4 wt%, or 5 wt%.
[0047] According to an embodiment of the present invention, the electrolyte satisfies:
[0048] 15≥C1≥0;
[0049] 5≥C2≥0;
[0050] 20≥C1+C2≥Z;
[0051] Wherein, C1 is the percentage of the mass of the fluoroethylene carbonate in the total mass of the electrolyte; C2 is the percentage of the mass of the sulfonic acid compound in the total mass of the electrolyte; and Z is the percentage of the mass of the third additive in the total mass of the electrolyte.
[0052] According to embodiments of the present invention, research has found that when the electrolyte satisfies 15≥C1≥0; 5≥C2≥0; 20≥C1+C2≥Z, the negative electrode protection additive can fully exert its function, forming sufficient protection on the negative electrode and reducing the deterioration of the negative electrode by polynitrile compounds. It also avoids excessive addition of the negative electrode protection additive leading to an excessively thick negative electrode film, increasing interfacial impedance, and deteriorating the battery's low-temperature performance. Simultaneously, the negative electrode protection additive can also reduce polarization during battery charging and discharging. Polarization refers to the change in potential difference between the positive and negative electrodes during charging and discharging, leading to a decrease in battery performance. Reducing the electrolyte's erosion of the negative electrode and forming an SEI film on the negative electrode surface helps maintain the stability of the negative electrode during charging and discharging, preventing large potential fluctuations. The SEI film formed by the negative electrode protection additive also has good ionic conductivity, allowing lithium ions to pass smoothly during charging and discharging while blocking electron transport. This selective conductivity helps reduce the charge transfer resistance between the electrode and electrolyte interface, improving the battery's charging and discharging efficiency. In other words, the negative electrode protection additive can reduce the polarization of the battery by stabilizing the electrode potential and reducing charge transfer resistance, thus enabling the battery to maintain better performance stability during charging and discharging. This is beneficial for improving the battery's high-temperature cycle performance and room-temperature cycle performance. Moreover, the SEI film formed on the negative electrode surface by the negative electrode protection additive not only does not hinder the passage of ions, but also promotes ion migration due to its good ionic conductivity. It can not only compensate for the slowed migration rate of ions in the electrolyte caused by low temperature, but also improve the overall migration rate of ions at low temperatures. Therefore, it can improve the low-temperature performance of the battery, reduce harmful heat generation and heat accumulation, improve furnace temperature performance, and improve the furnace temperature safety performance and low-temperature performance of the obtained battery.
[0053] When the electrolyte satisfies 15<C1 or 5<C2, the content of the negative electrode protection additive is excessively high. The negative electrode protection additive will not only form an excessively thick SEI film, increase the internal resistance and deteriorate the low-temperature performance of the battery, but also cause excessive negative electrode protection additive to occupy the space originally used for ion transport in the electrolyte, resulting in a decrease in the conductivity of the electrolyte. Excessive negative electrode protection additive may also undergo undesired chemical reactions with other components in the electrolyte, leading to unstable properties of the electrolyte. This instability will also trigger side reactions inside the battery, reducing the high-temperature cycle performance, room-temperature cycle performance and oven temperature safety performance of the battery. When the electrolyte satisfies C1+C2<Z, the content of the negative electrode protection additive is excessively low, the negative electrode protection additive cannot form sufficient protection on the surface of the negative electrode, and the improvement on the low-temperature performance, high-temperature cycle performance, room-temperature cycle performance and oven temperature safety performance of the battery is not significant.
[0054] According to the embodiment of the present invention, the sulfonic acid-based compounds include, but are not limited to, at least one of 1,3-propane sultone, 1-propene-1,3-sultone, 5-methyl oxathiolane 2,2-dioxide, 1,3-propene sultone, 2,4-butane sultone, 1,4-butane sultone, 1,3-butane sultone, and fluorinated 1,3-propane sultone.
[0055] According to the embodiment of the present invention, the electrolyte further includes an electrolyte lithium salt.
[0056] According to the embodiment of the present invention, the electrolyte lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiTFSI), lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalato)phosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methide, or lithium bis(trifluoromethylsulfonyl)imide.
[0057] According to the embodiment of the present invention, the electrolyte further includes an organic solvent, the organic solvent is selected from carbonate and / or carboxylate, the carbonate is selected from one or more of the following fluorinated or unsubstituted solvents: ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate, diethyl carbonate (DEC), ethyl methyl carbonate; the carboxylate is selected from one or more of the following fluorinated or unsubstituted solvents: propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, propyl propionate (PP), ethyl propionate (EP), methyl butyrate, and ethyl n-butyrate.
[0058] According to the embodiment of the present invention, the electrolyte is used in batteries, for example, in lithium ion batteries.
[0059] According to an embodiment of the present invention, the electrolyte is a non-aqueous electrolyte.
[0060] The present invention also provides a battery comprising the electrolyte described above.
[0061] According to an embodiment of the present invention, the battery further includes a positive electrode sheet containing a positive electrode active material, a negative electrode sheet containing a negative electrode active material, and a separator.
[0062] According to an embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active material layer coated on one or both surfaces of the positive current collector, wherein the positive active material layer includes a positive active material, a conductive agent, and a binder.
[0063] According to embodiments of the present invention, the single-sided coating thickness of the positive electrode active material layer is 20-65 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, or 65 μm. When the single-sided coating thickness of the positive electrode active material layer is <20 μm, firstly, the battery capacity will be lower; secondly, an excessively thin positive electrode active material layer will make the positive electrode active material prone to structural changes or dissolution, deteriorating the battery's cycle performance and increasing safety risks such as internal short circuits and explosions. When the single-sided coating thickness of the positive electrode active material layer is >65 μm, lithium-ion permeability will be reduced, internal resistance will increase, and the positive electrode active material will not be fully utilized during battery charging and discharging. Furthermore, an excessively thick single-sided coating thickness of the positive electrode active material layer will require more polynitrile compounds to protect the positive electrode. Too many polynitrile compounds will also increase the battery's internal resistance, requiring more negative electrode protection additives to mitigate their deterioration on the negative electrode. Too many additives will lead to a decrease in battery cycle performance.
[0064] According to an embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one or both surfaces of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.
[0065] According to an embodiment of the present invention, the mass percentage of each component in the positive electrode active material layer is: 80-99.8 wt% positive electrode active material, 0.1-10 wt% conductive agent, and 0.1-10 wt% binder.
[0066] Preferably, the mass percentage of each component in the positive electrode active material layer is: 90-99.6 wt% positive electrode active material, 0.2-5 wt% conductive agent, and 0.2-5 wt% binder.
[0067] According to the embodiment of the present invention, the mass percentage of each component in the negative electrode active material layer is: 80 to 99.8 wt% of the negative electrode active material, 0.1 to 10 wt% of the conductive agent, and 0.1 to 10 wt% of the binder.
[0068] Preferably, the mass percentage of each component in the negative electrode active material layer is: 90 to 99.6 wt% of the negative electrode active material, 0.2 to 5 wt% of the conductive agent, and 0.2 to 5 wt% of the binder.
[0069] According to the embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, and metal powder.
[0070] According to the embodiment of the present invention, the binder is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.
[0071] According to the embodiment of the present invention, the negative electrode active material includes a carbon-based negative electrode material.
[0072] According to the embodiment of the present invention, the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0073] According to the embodiment of the present invention, studies have found that the electrolyte of the present invention is more suitable for carbon-based negative electrode materials, because the carbon-based negative electrode material has smaller volume expansion, the SEI film formed by the electrolyte on the surface of the carbon-based negative electrode material is not prone to continuous rupture due to volume expansion and continuous consumption of the electrolyte to form the SEI film, nor will the performance deteriorate rapidly due to the continuous consumption of the electrolyte and the lithium source.
[0074] According to the embodiment of the present invention, the negative electrode active material may further include a silicon-based negative electrode material.
[0075] According to the embodiment of the present invention, the silicon-based negative electrode material is selected from at least one of nano-silicon (Si), silicon oxide negative electrode material (SiOx, 0<x<2) and silicon-carbon negative electrode material.
[0076] According to the embodiment of the present invention, the positive electrode active material is selected from one or more of transition metal lithium oxides, lithium iron phosphate, and lithium manganate; the chemical formula of the transition metal lithium oxide is Li 1+a Ni x Co y M z O2, where -0.1≤a≤1; 0≤x≤1, 0<y≤1, 0≤z≤1; wherein M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0077] According to embodiments of the present invention, since the electrolyte has high electrochemical stability and a wide electrochemical window, it is well compatible with lithium cobalt oxide cathode materials. When lithium cobalt oxide is used as the cathode material, the advantages of the electrolyte can be fully utilized, giving the battery the advantages of high energy density and fast charge and discharge.
[0078] According to embodiments of the present invention, the pore size of the separator is 0.02-0.07 μm, for example, 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, or 0.07 μm. Studies have found that when the pore size of the separator is too small (<0.02 μm), it hinders the normal passage rate of lithium ions through the separator, increases internal resistance, and deteriorates the battery's cycle performance. When the pore size of the separator is too large, lithium ions migrate faster during charging and discharging, easily leading to uneven distribution of lithium ions at the negative electrode, increasing the risk of lithium plating, and thus affecting the battery's cycle performance. Furthermore, an excessively large pore size also reduces the mechanical strength of the separator, making it more prone to deformation or damage during charging and discharging, further deteriorating the battery's cycle performance. Uneven lithium ion distribution can also lead to dendrite growth; when the separator pore size is too large and mechanical strength is reduced, the probability of dendrites piercing the separator increases, reducing safety performance. When the pore size of the separator is 0.02-0.07μm, it has higher compatibility with hydrocarbon amine compounds, does not affect the passage of lithium ions during normal charging and discharging, has strong resistance to lithium ion passage at high temperatures, and ensures the cycle performance and furnace temperature safety performance of the battery.
[0079] The beneficial effects of this invention are:
[0080] This invention provides an electrolyte and a battery comprising the electrolyte. The electrolyte includes a first additive and a second additive; the first additive includes a hydrocarbon-based amine compound, and the second additive includes a sulfate ester compound. The electrolyte improves the battery's furnace temperature safety and low-temperature performance. The electrolyte of this invention forms a protective SEI / CEI film on the surfaces of the positive and negative electrodes, maintaining structural and functional stability even under high temperatures or thermal runaway conditions, thus improving battery safety issues caused by SEI / CEI film failure. The electrolyte additives of this invention also reduce electrolyte viscosity and solvate with solvent molecules, allowing ions to maintain high mobility even at lower temperatures, improving ionic conductivity, reducing battery impedance, and thereby improving the battery's low-temperature performance. Detailed Implementation
[0081] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0082] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0083] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0084] The pore size testing process for the diaphragm used in the following embodiments is as follows: 1. A diaphragm disc with a diameter of 24 mm is punched out using a slicer. Then, the sample is completely wetted with a special wetting solution with a surface tension of 15.9 dynes / cm. Next, a gas that does not react with the wetting solution or the sample is used to compress the wetting solution within the sample pores. As the pressure increases, the through-holes (holes connecting one end of the material to the other) are gradually emptied from large to small. By testing the relationship between the pressure and flow rate of the gas, the pore size distribution data can be obtained.
[0085] Examples 1-22 and Comparative Examples 1-3
[0086] 1) Preparation of positive electrode sheet
[0087] Lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), super P (SP), and carbon nanotubes (CNTs) were mixed in a mass ratio of 96:2:1.5:0.5. N-methylpyrrolidone (NMP) was added, and the mixture was stirred under vacuum until a uniform and fluid positive electrode active slurry was formed. The positive electrode active slurry was uniformly coated onto both surfaces of an aluminum foil. The coated aluminum foil was dried, and then rolled and slit to obtain the desired positive electrode sheet. The single-sided coating thickness of the positive electrode active material layer formed by the positive electrode active slurry was 35 μm.
[0088] 2) Preparation of negative electrode sheet
[0089] The negative electrode active materials, artificial graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP), and single-walled carbon nanotubes (SWCNTs), were mixed in a mass ratio of 94.5:2.5:1.5:1:0.5. Deionized water was added, and the mixture was stirred in a vacuum mixer to obtain a negative electrode active slurry. The negative electrode active slurry was uniformly coated on both surfaces of a copper foil. The coated copper foil was dried at room temperature and then transferred to an 80°C oven for 10 hours. After cold pressing and slitting, the negative electrode sheet was obtained.
[0090] 3) Preparation of electrolyte
[0091] In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), EC / PC / DEC / PP were mixed uniformly at a mass ratio of 10:20:20:50. Then, 14 wt% of fully dried lithium hexafluorophosphate (LiPF6) based on the total electrolyte mass was quickly added and dissolved. Following this, X wt% of the first additive based on the total electrolyte mass was added, followed by Y wt% of the second additive based on the total electrolyte mass, as shown in Table 1. After thorough mixing, and after passing moisture and free acid tests, the desired electrolyte was obtained.
[0092] 4) Preparation of the diaphragm
[0093] The diaphragm is made of polyethylene with a thickness of 9μm and an average pore size of 50nm.
[0094] 5) Preparation of lithium-ion batteries
[0095] The positive electrode sheet from step 1), the negative electrode sheet from step 2), and the separator are stacked in the order of positive electrode sheet, separator, and negative electrode sheet, and then wound to obtain a battery cell. The battery cell is placed in an outer packaging aluminum foil, and the electrolyte from step 3) is injected into the outer packaging. After vacuum sealing, settling, formation, shaping, and sorting, a lithium-ion battery is obtained. The charge / discharge range of the battery of this invention is 3.0-4.53V.
[0096] The lithium-ion batteries obtained in the examples and comparative examples were subjected to DCIR tests at 0°C, cycle performance tests at 0°C, cycle performance tests at 25°C, thermal performance tests, and cycle performance tests at 45°C. The test results are shown in Table 2.
[0097] 1) 0℃ DCIR test
[0098] The batteries obtained in the examples and comparative examples were subjected to the following conditions at room temperature: 0.5C lower voltage, 0.5C charging to upper voltage, constant voltage charging to 0.05C, 0.5C discharging to 3V, and 0.5C charging to 50% SOC. The electrochemical device was then left to stand at 0°C for 4 hours. The following sampling was performed: 0.1C discharge for 10 seconds with a sampling interval of 0.01s, followed by a 40-second rest period with a sampling interval of 5s; 0.1C charging for 10 seconds with a sampling interval of 0.01s; resting for 40 seconds with a sampling interval of 5s; 0.3C discharge for 10 seconds with a sampling interval of 0.01s; resting for 40 seconds with a sampling interval of 5s; and 0.3C charging for 10 seconds with a sampling interval of 0.01s. Based on the DCIR calculation method: voltage difference / current difference = DCIR, the charging DCIR and discharging DCIR of the electrochemical device at 0°C were obtained.
[0099] 2) 0℃ Cyclic Performance Test
[0100] The batteries obtained in the examples and comparative examples were charged at 0°C with a constant current of 0.5C to a voltage of 4.53V, then charged at 4.53V with a constant voltage to a current of 0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 0.5C to a voltage of 3.0V. This constitutes one charge-discharge cycle. The discharge capacity of the first week was measured as x mAh, and the discharge capacity of the Nth week was measured as y mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R = y / x. The capacity retention rate of the battery was recorded after 500T cycles.
[0101] 3) 25℃ Cyclic Performance Test
[0102] The batteries obtained in the examples and comparative examples were charged at 25°C with a constant current of 0.5C to a voltage of 4.53V, then charged at 4.53V with a constant voltage to a current of 0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 0.5C to a voltage of 3.0V. This constitutes one charge-discharge cycle. The discharge capacity of the first week was measured as x mAh, and the discharge capacity of the Nth week was measured as y mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R = y / x. The capacity retention rate of the battery was recorded after 500T cycles.
[0103] 4) Hot Box Performance Test
[0104] At room temperature, the batteries obtained in the examples and comparative examples were charged to 4.5V at a constant current of 1C, left to stand for 60 minutes, and their appearance was inspected and photographed. Then, the temperature was increased to 132℃±2℃ at a rate of 3℃ / min±2℃ / min and held for 60 minutes. The samples were observed; those that did not leak, smoke, ignite, or explode were considered to have passed the test. Ten samples were tested for each example or comparative example, and the pass rate of the hot-box performance test was recorded.
[0105] 5) 45℃ Cyclic Performance Test
[0106] The batteries obtained in the examples and comparative examples were charged at 45°C with a constant current of 0.5C to a voltage of 4.53V, then charged at 4.53V with a constant voltage to a current of 0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 0.5C to a voltage of 3.0V. This constitutes one charge-discharge cycle. The discharge capacity of the first week was measured as x mAh, and the discharge capacity of the Nth week was measured as y mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R = y / x. The capacity retention rate of the battery was recorded after 500T cycles.
[0107] Table 1. Composition of electrolyte in batteries of Examples 1-22 and Comparative Examples 1-3
[0108]
[0109] Table 2. Performance test results of batteries in Examples 1-22 and Comparative Examples 1-3.
[0110]
[0111]
[0112] A comparison of Tables 1 and 2 shows that the electrolyte with both the first and second additives can improve the furnace temperature safety and low-temperature performance of the battery. Adjusting the mass ratios of the first and second additives can also adjust these performance characteristics. Furthermore, when the electrolyte satisfies 0.1 ≤ X / (Y+2) ≤ 1, the effects of the first and second additives can be fully utilized, resulting in optimal furnace temperature safety and low-temperature performance of the battery.
[0113] Examples 23-34
[0114] The other operations are the same as in Example 2, except for the preparation of the electrolyte.
[0115] In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), EC / PC / DEC / PP were mixed uniformly at a mass ratio of 10:20:20:50. Then, 14 wt% of fully dried lithium hexafluorophosphate (LiPF6) based on the total electrolyte mass was quickly added and dissolved. Following this, 1 wt% of compound (I-4) based on the total electrolyte mass was added, followed by 2 wt% of compound (II-1) based on the total electrolyte mass, and then 2 wt% of a third additive based on the total electrolyte mass. The specific amounts added are shown in Table 2. After thorough mixing, and after passing moisture and free acid tests, the desired electrolyte was obtained.
[0116] Table 3. Composition of electrolyte in batteries of Examples 23-34
[0117] Example 2 / 3 Example 23 HTCN / 0.5wt% 3.5 Example 24 HTCN / 1wt% 4 Example 25 HTCN / 2wt% 5 Example 26 HTCN / 5wt% 8 Example 27 HTCN / 7wt% 10 Example 28 HTCN / 8wt% 11 Example 29 ADN / 1wt%; SN / 2wt%; HTCN / 2wt% 8 Example 30 SN / 2wt% 5 Example 31 ADN / 2wt% 5 Example 32 1,3,5-Cyclohexanetrionitrile / 2wt% 5 Example 33 1,1,3,3-propanetetracarbonyl nitrile / 2wt% 5 Example 34 1,2,2,3-Tetracyanopropane / 2wt% 5
[0118] Table 4. Performance test results of batteries in Examples 23-34
[0119]
[0120] The performance test results in Tables 3 and 4 show that the introduced polynitrile compounds, acting as a third additive, work in conjunction with sulfate compounds on the surfaces of the positive and negative electrodes to form a stable and thin interfacial film. This effectively reduces the impedance of the electrode interface and improves the battery's low-temperature performance, high-temperature cycle performance, and furnace temperature safety performance. When the electrolyte satisfies 0.3≤X+Y+Z≤9, the combined effect of the polynitrile compounds and sulfate compounds can fully occur, further enhancing the battery's low-temperature performance, high-temperature cycle performance, and furnace temperature safety performance.
[0121] Examples 35-49
[0122] The other operations are the same as in Example 29, except that the electrolyte preparation...
[0123] In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), EC / PC / DEC / PP were mixed uniformly at a mass ratio of 10:20:20:50. Then, 14 wt% of fully dried lithium hexafluorophosphate (LiPF6) based on the total electrolyte mass was quickly added and dissolved. After dissolution, 1 wt% of compound (I-4) based on the total electrolyte mass was added, followed by 2 wt% of compound (II-1) based on the total electrolyte mass, then 1 wt% of ADN, 2 wt% of SN, 2 wt% of HTCN, C1 of fluoroethylene carbonate based on the total electrolyte mass, and C2 of sulfonic acid compounds based on the total electrolyte mass. The specific amounts added are shown in Table 3. After thorough mixing, and after passing moisture and free acid tests, the desired electrolyte was obtained.
[0124] Table 5. Composition of the electrolyte in the batteries of Examples 35-49
[0125]
[0126]
[0127] Table 6 Performance test results of batteries in Examples 35-49
[0128]
[0129] As can be seen from Tables 5 and 6, when the electrolyte satisfies 15≥C1≥0; 5≥C2≥0; 20≥C1+C2≥Z, it can fully exert the role of the negative electrode protection additive, so that it can form sufficient protection on the negative electrode, which is beneficial to improving the high temperature cycle performance and room temperature cycle performance of the battery, and also improves the furnace temperature safety performance and low temperature performance of the battery.
[0130] Examples 50-57
[0131] The other operations are the same as in Example 46, except that the preparation of the separator and the preparation of the positive electrode are different.
[0132] Polyethylene separators with different pore sizes and a thickness of 9 μm and positive electrode sheets with different single-sided coating thicknesses were selected.
[0133] Table 7. Composition of the separator and positive electrode in the batteries of Examples 50-57
[0134] Example 46 0.05 35 Example 50 0.01 35 Example 51 0.08 35 Example 52 0.05 10 Example 53 0.05 70 Example 54 0.03 35 Example 55 0.07 35 Example 56 0.05 25 Example 57 0.05 45
[0135] Table 8 Performance test results of batteries in Examples 50-57
[0136]
[0137] As can be seen from the performance test results in Tables 7 and 8, by adjusting the single-sided coating thickness of the positive electrode active material layer and the pore size of the separator, and ensuring that the single-sided coating thickness of the positive electrode active material layer is 20-65 μm and the pore size of the separator is 0.02-0.07 μm, the cycle performance and furnace temperature safety performance of the battery can be balanced.
[0138] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that, The electrolyte includes an electrolyte additive, which includes a first additive and a second additive; the first additive includes a hydrocarbon amine compound, which is selected from at least one compound of the structural formula shown in formula (I): Equation (I) In formula (Ⅰ), R1, R2, and R3 may be the same or different, and are independently selected from H, halogens, substituted or unsubstituted C1-C atoms. 12 Alkyl, substituted or unsubstituted C2-C 12 alkenyl, substituted or unsubstituted C2-C 12 Alkyne group, substituted or unsubstituted C3-C 12 Cycloalkyl; if substituted, the substituent is C1-C. 12 Alkyl or halogen; or, R1 is selected from H, halogen, substituted or unsubstituted C1-C. 12 Alkyl, substituted or unsubstituted C2-C 12 alkenyl, substituted or unsubstituted C2-C 12 Alkyne group, substituted or unsubstituted C3-C 12 Cycloalkyl; if substituted, the substituent is C1-C. 12 Alkyl or halogen; R2 and R3 form substituted or unsubstituted C3-C rings. 12 Cycloalkyl; if substituted, the substituent is C1-C. 12 Alkyl or halogen; The second additive includes a sulfate ester compound, said sulfate ester compound being selected from at least one compound of the structural formula shown in formula (II): Formula (II) In equation (II), n is 0 or 1, m is 0 or 1, p is 0 or 1, and X1, X2, and X3 may be the same or different, and are independently selected from each other. , or And at least one of the groups X1, X2, and X3 is selected from or , This is the connection point.
2. The electrolyte according to claim 1, characterized in that, In formula (Ⅰ), R1, R2, and R3 may be the same or different, and are independently selected from H, halogens, substituted or unsubstituted C1-C6 alkyl groups, substituted or unsubstituted C2-C6 alkenyl groups, substituted or unsubstituted C2-C6 alkynyl groups, and substituted or unsubstituted C3-C6 cycloalkyl groups; if substituted, the substituents are C1-C6 alkyl groups or halogens; or, R1 is selected from H, halogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 ynyl, substituted or unsubstituted C3-C6 cycloalkyl; if substituted, the substituent is C1-C6 alkyl or halogen; R2 and R3 form a substituted or unsubstituted C3-C6 cycloalkyl after cyclization; if substituted, the substituent is C1-C6 alkyl or halogen.
3. The electrolyte according to claim 2, characterized in that, In formula (Ⅰ), R1, R2, and R3 may be the same or different, and are independently selected from H, halogens, substituted or unsubstituted C1-C3 alkyl groups, substituted or unsubstituted C2-C3 alkenyl groups, substituted or unsubstituted C2-C3 alkynyl groups, and substituted or unsubstituted C3-C4 cycloalkyl groups; if substituted, the substituents are C1-C3 alkyl groups or halogens; or, R1 is selected from H, halogen, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C2-C3 alkenyl, substituted or unsubstituted C2-C3 alkynyl, substituted or unsubstituted C3-C4 cycloalkyl; if substituted, the substituent is C1-C3 alkyl or halogen; R2 and R3 form a substituted or unsubstituted C3-C4 cycloalkyl after cyclization; if substituted, the substituent is C1-C3 alkyl or halogen.
4. The electrolyte according to claim 1, characterized in that, In formula (I), the hydrocarbon amine compound includes at least one of the compounds with the structural formulas shown in formulas (I-1) to (I-8): 。 5. The electrolyte according to claim 1, characterized in that, The sulfate ester compounds include at least one of the compounds with the structural formulas shown in formulas (II-1) to (II-16) below: 。 6. The electrolyte according to any one of claims 1-5, characterized in that, The first additive accounts for 0.1wt%-5wt% of the total mass of the electrolyte.
7. The electrolyte according to claim 6, characterized in that, The first additive accounts for 0.5wt%-1.5wt% of the total mass of the electrolyte.
8. The electrolyte according to any one of claims 1-5, characterized in that, The second additive accounts for 0.1wt%-5wt% of the total mass of the electrolyte.
9. The electrolyte according to claim 8, characterized in that, The second additive accounts for 0.5wt%-3wt% of the total mass of the electrolyte.
10. The electrolyte according to any one of claims 1-5, characterized in that, The electrolyte satisfies the following: 0.1≤X / (Y+2)≤1; Where X is the percentage of the first additive in the total mass of the electrolyte; Y is the percentage of the second additive in the total mass of the electrolyte.
11. The electrolyte according to any one of claims 1-5, characterized in that, The electrolyte additive further includes a third additive selected from polynitrile compounds, including at least one of the following: dinitrile compounds represented by formula (Ⅲ-1), trinitrile compounds represented by formula (Ⅲ-2), and tetranitrile compounds represented by formula (Ⅲ-3). Wherein, R4 is a group having 1-10 carbon atoms with at least 2 substitution positions; R5 is a group having 1-10 carbon atoms with at least 3 substitution positions; and R6 is a group having 1-10 carbon atoms with at least 4 substitution positions, wherein the group having 1-10 carbon atoms is selected from substituted or unsubstituted C atoms. 1-10 Alkyl, substituted or unsubstituted C 5-10 heteroaryl, substituted or unsubstituted C 6-10 Aryl.
12. The electrolyte according to claim 11, characterized in that, The dinitrile compound represented by formula (Ⅲ-1) is selected from at least one of the following compounds: succinate (SN), glutaronitrile, adiponitrile (ADN), sebaconitrile, anonadionitrile, dicyanophenylene, terephthalonitrile, pyridine-3,4-dianitrile, 2,5-dicyanopyridine, 3,3-[1,2-ethylenedimethylbis(oxy)]bispropionitrile, and trans-butenedionitrile; And / or, the trinitrile compound represented by formula (Ⅲ-2) is selected from at least one of the following compounds: 1,3,6-hexanetrionitrile (HTCN), 1,3,5-cyclohexanetrionitrile, 1,3,5-phenyltricyanide, 1,2,3-propanetrionitrile, glyceroltrionitrile; And / or, the tetranitrile compound represented by formula (Ⅲ-3) is selected from at least one of the following compounds: 1,1,3,3-propanetetracarbonyl, 1,2,2,3-tetracyanopropane, 1,2,4,5-tetracyanobenzene, 2,3,5,6-pyrazinetetranitrile, 7,7,8,8-tetracyano-p-benzodiquinone dimethyl ether, and tetracyanoethylene.
13. The electrolyte according to claim 11, characterized in that, The third additive accounts for 0.1wt%-7wt% of the total mass of the electrolyte.
14. The electrolyte according to claim 13, characterized in that, The third additive accounts for 2wt%-5.5wt% of the total mass of the electrolyte.
15. The electrolyte according to claim 11, characterized in that, The electrolyte satisfies the following: 0.3≤X+Y+Z≤9; Wherein, X is the percentage of the first additive by mass in the total mass of the electrolyte; Y is the percentage of the second additive by mass in the total mass of the electrolyte; and Z is the percentage of the third additive by mass in the total mass of the electrolyte.
16. The electrolyte according to any one of claims 1-5, characterized in that, The electrolyte also includes a negative electrode protection additive, which includes fluoroethylene carbonate and sulfonic acid compounds.
17. The electrolyte according to claim 11, characterized in that, The electrolyte also includes a negative electrode protection additive, which includes fluoroethylene carbonate and sulfonic acid compounds.
18. The electrolyte according to claim 17, characterized in that, The electrolyte satisfies the following: 15≥C1≥0; 5≥C2≥0; 20≥C1+C2≥Z; Wherein, C1 is the percentage of the mass of the fluoroethylene carbonate in the total mass of the electrolyte; C2 is the percentage of the mass of the sulfonic acid compound in the total mass of the electrolyte; and Z is the percentage of the mass of the third additive in the total mass of the electrolyte.
19. A battery, characterized in that, The battery comprises the electrolyte according to any one of claims 1-18.
20. The battery according to claim 19, characterized in that, The battery also includes a positive electrode sheet containing positive active material, a negative electrode sheet containing negative active material, and a separator.
21. The battery according to claim 20, characterized in that, The positive electrode sheet includes a positive current collector and a positive active material layer coated on one or both surfaces of the positive current collector, wherein the single-sided coating thickness of the positive active material layer is 20-65 μm.
22. The battery according to claim 20, characterized in that, The pore size of the diaphragm is 0.02-0.07 μm.
Citation Information
Patent Citations
Silicon-carbon system lithium ion battery electrolyte and silicon-carbon system lithium ion battery
CN108878976A
Lithium-ion battery
WO2024032173A1
